DETERMINAÃ‡ÃƒO DO CÃLCIO EM PLANTAS PELO MÃ‰TODO DO GLIOXAL-BIS (2-HIDROXIANIL) - Bittencourt, V. C.; Catani, R. A.; Bergamin Filho, H. (REVISTA DE AGRICULTURA, 2015)
DETERMINAÃ‡ÃƒO DO CÃLCIO EM PLANTAS PELO MÃ‰TODO DO GLIOXAL-BIS (2-HIDROXIANIL)